Surface characterization of nanoparticles using near-field light scattering - Yoo, Eunsoo; Liu, Yizhong; Nwasike, Chukwuazam A.; Freeman, Sebastian R.; DiPaolo, Brian C.; Cordovez, Bernardo; Doiron, Amber L. (Beilstein Journal of Nanotechnology, 2018)
The effect of nanoparticle surface coating characteristics on colloidal stability in solution is a critical parameter in understanding the potential applications of nanoparticles, especially in biomedicine. Here we explored the modification of the surface of poly(ethylene glycol)-coated superparamagnetic iron oxide nanoparticles (PEG-SPIOs) with the synthetic pseudotannin polygallol via interpolymer complexation (IPC). Changes in particle size and zeta potential were indirectly assessed via differences between PEG-SPIOs and IPC-SPIOs in particle velocity and scattering intensity using near-field light scattering. The local scattering intensity is correlated with the distance between the particle and waveguide, which is affected by the size of the particle (coating thickness) as well as the interactions between the particle and waveguide (related to the zeta potential of the coating). Therefore, we report here the use of near-field light scattering using nanophotonic force microscopy (using a NanoTweezerTM instrument, Halo Labs) to determine the changes that occurred in hydrated particle characteristics, which is accompanied by an analytical model. Furthermore, we found that altering the salt concentration of the suspension solution affected the velocity of particles due to the change of dielectric constant and viscosity of the solution. These findings suggest that this technique is suitable for studying particle surface changes and perhaps can be used to dynamically study reaction kinetics at the particle surface.
Keywords: nanoparticle surface properties; nanoparticles; nanophotonic force microscopy; near-field light scattering; superparamagnetic iron oxide